Assessing the Functional Limitations of Lipids and Fatty Acids for Diet Determination: The Importance of Tissue Type, Quantity, and Quality - Meyer, Lauren; Pethybridge, Heidi; Nichols, Peter D.; Beckmann, Crystal; Bruce, Barry D.; Werry, Jonathan M.; Huveneers, Charlie (Frontiers in Marine Science, 2017)
Lipid and fatty acid (FA) analysis is commonly used to describe the trophic ecology of an increasing number of taxa. However, the applicability of these analyses is contingent upon the collection and storage of sufficient high quality tissue, the limitations of which are previously unexplored in elasmobranchs. Using samples from 110 white sharks, Carcharodon carcharias, collected throughout Australia, we investigated the importance of tissue type, sample quantity, and quality for reliable lipid class and FA analysis. We determined that muscle and sub-dermal tissue contain distinct lipid class and FA profiles, and were not directly comparable. Muscle samples as small as 12 mg dry weight (49 mg wet weight), provided reliable and consistent FA profiles, while sub-dermal tissue samples of 40 mg dry weight (186 mg wet weight) or greater were required to yield consistent profiles. This validates the suitability of minimally invasive sampling methods such as punch biopsies. The integrity of FA profiles in muscle was compromised after 24 hours at ambient temperature (~20°C), making these degraded samples unreliable for accurate determination of dietary sources, yet sub-dermal tissue retained stable FA profiles under the same conditions, suggesting it may be a more robust tissue for trophic ecology work with potentially degraded samples. However, muscle samples archived for up to 16 years in -20°C retain their FA profiles, highlighting that tissue from museum or private collections can yield valid insights into the trophic ecology of marine elasmobranchs.